How To Conduct a Follow-Up Study of Special Education Graduates - Kearns, Donna; Missouri Univ., Columbia. Coll. of Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This guide is designed to assist Missouri school district personnel in conducting follow-up studies of special education graduates. The guide outlines the questions that need to be addressed prior to conducting a follow-up study as well as the procedures to complete such a project. Sample follow-up questionnaires are included for districts to replicate and use in district studies. The questionnaires include areas to be addressed through district records, student interviews, and parent interviews. Selected descriptive and graphic displays of follow-up study results are included in the guide as examples. Five references are also included. (KC)
Availability: Instructional Materials Laboratory, 10 London Hall, University of Missouri, Columbia, MO 65211.
Sponsoring Agency: Missouri State Dept. of Elementary and Secondary Education, Jefferson City. Div. of Special Education.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Community Programs; Graduate Surveys; Guidelines; High School Graduates; High Schools; Outcomes of Education; Program Effectiveness; Program Evaluation; Research Methodology; Special Education; State Programs; Missouri; Guides, Non-Classroom.; Tests/Questionnaires.